Penerapan Program Sosialisasi Pendidikan Karakter di SDN Musir Kidul - Chrystia Aji Putra; Sulaicha Sulaicha; Firman Lucky Saputra; Salsabila Putri Ramadhani; Selfa Eka Ramadhani; Wardah Firdausil Kamala (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
Character education has become the primary focus in efforts to develop individuals with strong moral values and ethics. In the context of modern education, character education goes beyond teaching discipline or enforcing rules; it strengthens the core of good personality and fosters positive behaviors in daily life. This paper reviews character education from various perspectives, including the conceptual understanding, implementation approaches in educational institutions, and its impact on shaping a better future generation. By integrating values such as integrity, empathy, honesty, and responsibility, character education plays a crucial role in shaping individuals who are not only academically competent but also ethically sound and capable of making positive contributions to society. Through a profound understanding of these values, educational institutions can play a crucial role in laying a solid moral foundation for future generations.